INTERACTIVE ANIMATION FOR INTRODUCING JAPANESE LANGUAGE (HIRAGANA, KATAKANA, DAYS OF THE WEEK, NUMBERS, AND KANJI) BASED ON WEB - Ahmad Rafik; Adika May Sari; Amas Sari Marthanti; Desy Suryani; Rosmita (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The utilization of creative and innovative technology as a medium for learning can be developed well if the community can make use of it. Animation is a science that combines elements of art with technology. Therefore, a web-based Japanese language learning medium has been designed, combined with simple interactive animation videos. Language is a tool for social communication in the form of a system of sounds produced by human speech. Language is categorized as one of the elements of culture. Therefore, many languages emerge in the world. This learning medium contains materials on hiragana, katakana, days of the week, and numbers. The result of this design is a simple Japanese language learning animation with materials and practice questions that can be used for evaluation. In addition, this animation can also be accessed anytime and anywhere, making it easier for users to learn Japanese.